Inherited neuropathies - Reilly, Mary M. (Henry Stewart Talks, 2014)
Inherited neuropathies, Charcot Marie Tooth disease is the commonest inherited neuropathy, Four genes out of 78 account for over 60% of the cases of CMT, Genotype / phenotype correlations explored, Role of next generation sequencing discussed